2018
DOI: 10.1111/hsc.12591
|View full text |Cite
|
Sign up to set email alerts
|

Integrating social engagement instruments into Australian community aged care assessments to enhance service provision

Abstract: Rich social relationships contribute to improved well-being and health outcomes, yet aged care client assessments tend to focus almost exclusively on physical issues. We aim to explore the experiences of aged care staff following their use of social engagement and well-being instruments as part of routine assessments for home-care clients. The social engagement (Australian Community Participation Questionnaire, ACPQ) and well-being (ICEpop CAPability Measure for Older Adults, ICECAP-O) instruments were embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…This included multiple working group meetings, examining deficiencies and aligning with the provider’s aims. Ultimately, by working collaboratively over a long period of time, encompassing multiple research opportunities (psychosocial tool selection and software implementation),19 20 a successful forum was made possible.…”
Section: Discussionmentioning
confidence: 99%
“…This included multiple working group meetings, examining deficiencies and aligning with the provider’s aims. Ultimately, by working collaboratively over a long period of time, encompassing multiple research opportunities (psychosocial tool selection and software implementation),19 20 a successful forum was made possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work identified that staff reported numerous benefits, as well as barriers, when completing the social participation and QoL tools with their clients . One critical issue commonly identified by staff was the inability to capture relevant information within the electronic assessment forms that could potentially influence service provisions (eg a client's goals and barriers to services).…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier work identified that staff reported numerous benefits, as well as barriers, when completing the social participation and QoL tools with their clients. 7 One critical issue commonly identified by staff was the inability to capture relevant information within the electronic assessment forms that could potentially influence service provisions (eg a client's goals and barriers to services). This led to the formation of iterative think tank sessions to understand what information was considered important for staff to help improve care planning, and how this information could be captured in the current ICT system without burdening staff.…”
Section: Planmentioning
confidence: 99%
See 2 more Smart Citations